EDUKASI LITERASI KEUANGAN KELUARGA MELALUI PROGRAM GERAKAN KELUARGA MASLAHAT DI KABUPATEN LOMBOK TIMUR - Siti Reuni Inayati; Sahrul Ihsan (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Family well-being is strongly influenced by the ability of family members to manage their financial resources effectively. Limited financial literacy often leads to difficulties in budgeting, recording income and expenses, building saving habits, and preparing emergency funds. This community service program aimed to enhance public understanding of family financial management through the Gerakan Keluarga Maslahat (Family Welfare Movement Program) organized by the Office of the Ministry of Religious Affairs of East Lombok Regency. The activity was conducted on October 9, 2025, at Al Hilal Paok Pampang Mosque, Labuhan Haji District, involving 30 participants. The program employed participatory educational methods, including lectures, interactive discussions, question-and-answer sessions, and participatory evaluation. The results demonstrated an improvement in participants' understanding of family financial planning, household budgeting, simple financial record-keeping, saving habits, and the importance of establishing emergency funds. In addition, participants showed a more positive attitude toward managing household finances, as reflected in their increased awareness of prioritizing essential needs and implementing routine financial records. The active participation observed during discussions indicated that the educational materials were relevant to the participants' needs and daily financial challenges. Overall, the program contributed to strengthening family financial literacy as an effort to improve family resilience and long-term welfare.